Price transmission in whole milk powder markets: implications for the Oceania dairy sector of changing market developments. Issue 2 (3rd April 2017) - Zhang, Jing; Brown, Colin; Dong, Xiaoxia; Waldron, Scott
ABSTRACT: Recent developments in Asian dairy markets have significant implications for the Oceania (OC) dairy sector and especially whole milk powder markets. However, Asia is supplied not only by OC but also by the European Union (EU) and United States (US). Vector error correction models are used to analyse price relationships and market integration using monthly price data from January 2006 to December 2015. The results suggest that prices of whole milk powder in OC, EU and US are not independent and are instead co-integrated in the long run. OC and EU affect each other and adjust their price deviations quickly. However, no obvious correlation exists between OC and US despite a unidirectional relationship from EU to US. As the OC dairy sector responds to changes in the Asian dairy market, particularly in China, these price interrelationships with other key suppliers need to be recognised.